Bartter’s syndrome type II due to a novel mutation in KCNJ1 gene presenting in adulthood as recurrent hypokalaemic periodic paralysis - Kandari, Sharon; Puri, Rohit; Cheluvaiah, Chandrashekar; Biswal, Anshuman; Singh, Arshdeep; Ahlawat, Parul (International Journal of Research in Medical Sciences, 2024)
Bartter’s syndrome affects salt reabsorption transporters in Henle's loop's thick ascending limb (TAL). Bartter’s syndrome type II begins in antenatal/neonatal period with an autosomal recessive pattern of inheritance due to mutation in the KCNJ1 gene. Renal disorder begins early. It is a disorder which usually presents in infancy but not in adulthood. We report a case of late onset Bartter’s syndrome type II due to a novel mutation in the KCNJ1 gene manifesting with bilateral medullary nephrocalcinosis and recurrent hypokalaemic periodic paralysis.